Integrative Synergies between BRI of China and Agenda 2063 of African Union: Reviewing the Policy Documents and Analyzing the Program for Infrastructure Development in Africa-Priority Action Plan 2 (PIDA-PAP 2) (2021-2030) - Muhmmad Amjad Raza; Dr. Abdul Basit Khan (Journal of Development and Social Sciences, 2024)
This study analyzes the diverse and burgeoning relationship between China and the African Union (AU) which has significant global implications. The primary focus of the study is to explore Chinese policy commitments, competitive dynamics, capacity-building plug-ins as well as measures taken for the development of infrastructure under Priority Action Plan 2 (PAP 2) which is a landmark initiative of Program for Infrastructure Development in Africa (PIDA) to develop hydroelectric power, railways, roads, ports and information and communications technology (ICT) sectors. Furthermore, the study reviews the interconnection between the AU’s African Integrated High-Speed Railway Network (AIHSRN) Project as a case-study of China’s endeavors for the development of railways within the AU member countries. This assessment propounds an understanding of the importance of infrastructure and logistics to form collaborations, boost connectivity, and promote African economic development. The study uses a qualitative method of reasoning to investigate the basis and impact of Chinese interest and involvement within the AU. It provides the relevant researchers, experts from academia and policy makers a deep insight into the true nature of Chinese engagement within the AU which makes this study a significant addition to the currently existing literature about China-AU economic relations.
Keywords: Agenda 2063; Belt & Road Initiative; China-African Union Economic Cooperation; Program for Infrastructure Development in Africa-Priority Action Plan 2